PENINGKATAN KEMAMPUAN MOTORIK KASAR ANAK MELALUI PERMAINAN TRADISIONAL SUNDA MANDA - Kiki Maulana; Euis Cici Nurunnisa (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Tarbiyah, Institut Agama Islam Darussalam (IAID) Ciamis Jawa Barat, 2018)
The purpose of this study was to improve the ability of teachers to develop plans for implementing learning, the ability of teachers to implement learning and increase the gross motor skills of third grade children in MI Jatinagara. So that the child's gross motor skills will increase through traditional Sundanese manda games. The method used is the Classroom Action Research (CAR) method which is commonly used with four stages that are passed, namely: 1) planning, 2) implementation, 3) observation and 4) reflection. After conducting research, the results show that: 1) The teacher has increased in preparing the learning implementation plan, the average value in the first cycle reaches a value of 79.36, the second cycle reaches a value of 88.56 and in Cycle III reaches a value of 95.12. 2) The teacher experienced an increase in implementing learning, with an average value in the first cycle reaching 78.60, second cycle reaching 89.20 and in the third cycle reaching 95.00. 3) The gross motor skills of class III children in MI Jatinagara have increased, with an average value in cycle I reaching 46.30, cycle II reaching 74.00 and in cycle III reaching 95.30. Thus, through the traditional Sundanese manda game, it turns out that it can improve children's gross motor skills